Influence of Several True-Solvent, Co-Solvent and Non-Solvent on Thinner in Coating Adhesion And Thickness Automotive Paint - Isma Wulansari; Andi Rusnaenah; Irma Agustiningsih Imdam (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2025)
Choosing better organic solvents and providing appropriate mixing ratios for thinner in the automotive paint industry. The research objects were true solvents, ethyl acetate, butyl acetate, and acetone; alcohol cosolvents are isopropyl alcohol, isobutyl alcohol; and non-solvents are n-heptane, propylene glycol, and mineral spirits. Adhesion and coating thickness by spray paint and turbidity of thinner were performed. The thinner dissolving rate was evaluated by immersing coated galvalume plates (50 mm × 50 mm × 0.4 mm) into thinner and recording the time required to dissolve the paint. Thinner testing was conducted using a spray method at 17 cm distance and 90° angle, with coating thickness measured by coating thickness gauge and adhesion evaluated using the ASTM D3359 tape test. The best Performance was observed in the 5:3:3 composition (EA:IPA:MS), which achieved a 5B adhesion rating and a coating thickness of 60.7 µm. This ratio also had the lowest turbidity value (0.11 ± 0.02 NTU). Based on the capability plot analysis, this composition demonstrated high process capability (Cp = 3.06; Cpk = 2.52), confirming its suitability as the optimal formulation for automotive thinner applications.